The Beginning and Development of the Theranostic Approach in Nuclear Medicine, as Exemplified by the Radionuclide Pair 86Y and 90Y - Frank Rösch; Hans Herzog; Syed M. Qaim (MDPI AG, 2017)
In the context of radiopharmacy and molecular imaging, the concept of theranostics entails a therapy-accompanying diagnosis with the aim of a patient-specific treatment. Using the adequate diagnostic radiopharmaceutical, the disease and the state of the disease are verified for an individual patient. The other way around, it verifies that the radiopharmaceutical in hand represents a target-specific and selective molecule: the "best one" for that individual patient. Transforming diagnostic imaging into quantitative dosimetric information, the optimum radioactivity (expressed in maximum radiation dose to the target tissue and tolerable dose to healthy organs) of the adequate radiotherapeutical is applied to that individual patient. This theranostic approach in nuclear medicine is traced back to the first use of the radionuclide pair 86Y/90Y, which allowed a combination of PET and internal radiotherapy. Whereas the β-emitting therapeutic radionuclide 90Y (t½ = 2.7 d) had been available for a long time via the 90Sr/90Y generator system, the β+ emitter 86Y (t½ = 14.7 h) had to be developed for medical application. A brief outline of the various aspects of radiochemical and nuclear development work (nuclear data, cyclotron irradiation, chemical processing, quality control, etc.) is given. In parallel, the paper discusses the methodology introduced to quantify molecular imaging of 86Y-labelled compounds in terms of multiple and long-term PET recordings. It highlights the ultimate goal of radiotheranostics, namely to extract the radiation dose of the analogue 90Y-labelled compound in terms of mGy or mSv per MBq 90Y injected. Finally, the current and possible future development of theranostic approaches based on different PET and therapy nuclides is discussed.